"I never had a thought about drowning". Exploring water safety attitudes and practices among older adults in Western Australia. (26th July 2021) - Abercromby, Meg; Crawford, Gemma; Nimmo, Lauren; Leavy, Justine E.
Abstract: Objectives: The aim of this study was to explore factors associated with drowning among older adults aged 65 years and over in Western Australia. Methods: This paper was concerned with illuminating older adults experience and perspectives of water safety and drowning prevention. The study used in‐depth, semi‐structured interviews (n = 15) to examine knowledge, attitudes, beliefs and behaviours. The interviews were analysed using a phenomenological hermeneutical interpretation whereby three steps were taken to identify common patterns of meaning from individual's lifeworld. Discussion: Interviews captured the voices of those who identified as swimmers and those who identified as nonswimmers and revealed nine constitutive patterns which support a central theme of life around water. This study provides insights into perceptions and experiences of water safety as individuals' age. The findings suggest individuals who perceived themselves as strong swimmers had a decreased perception of risk, while participants who self‐identified as weak swimmers were more likely to avoid risks and modified their behaviour accordingly. Findings highlighted low water safety literacy and suggest that older people not only underestimate their drowning risk, but also lack an understanding of the risk factors for drowning. So what?: The findings from this study will have a direct impact on the development of a WA health promotion program to prevent drowning among older adults.